TRADITION AND PERMANENCE OF THE TTRASTIKHON, THE MINI FABLE - Dezotti, Maria Celeste Consolin [UNESP] (Univ Estadual Paulista, Fundacao Editora Unesp, 2022)
In his fable The Shepherd and the Lion (VI.1), La Fontaine mentions a certain Greek who boasts/ of a laconic elegancy, since he always compresses his fables in four lines. To whom La Fontaine is referring? Babrius (1th century) is the first poet to write fables in greek verse. Among them, written in choliambic verses, we find a unique structure: fables compressed in four lines, the so called tetrastikhon. That shape was imitated by medieval writers, among them we highlight Ignatius Diaconus (9th century). Although Fontaine depreciates this kind of mini fable, it keeps challenging poets. Brazilian Literature has two fans of fable in quatrain: Anastacio do Bomsucesso (19th century) and Mario Quintana (20th century).
Keywords: Anast?cio do Bomsucesso; Fable; La Fontaine; M?rio Quintana; Quatrain; Tetr?stikhon